THE COMPARATIVE ANALYSIS OF PACKAGING DESIGN ELEMENT TO PURCHASING DECISION BETWEEN COCA COLA AND BIG COLA IN MANADO - Gessal, Putri (Universitas Sam Ratulangi, 2013)
Packaging can play a very interesting role in the success or failure of a product. Its success depends a lot on how it is designed by its creators. Packaging function to protect the contents of a product lies within the package design. It has the power to influence your choices, and with its carefully thought-out aesthetics can affect your emotions. This aim of the study comparative analysis of packaging design element to purchase decision between Coca Cola and Big Cola with packaging element: Color, Size, Graphics, Material, Brand, Product Information, Packaging Technology. Theories supporting research are packaging design element and purchase decision. The research using comparative research. A structured questionnaire was used to collect data and information from 100 respondents who were randomly selected. This results have significant in purchase decision based on packaging design element between Coca cola and Big Cola in Manado and brand is the most influential element. Company need to develop their product to make more varieties and also develop product promotion. Keywords: packaging design element, purchase decision